2011
DOI: 10.1111/j.1548-2456.2011.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Voting and Life Satisfaction in Latin America

Abstract: What is the relationship between voting and individual life satisfaction in Latin America? While studies of Western Europe suggest that voters are happier than nonvoters, this relationship has not been explored in the younger democracies of the developing world, including those of Latin America. Using multilevel regression models to examine individual‐level survey data, this study shows a positive correlation between voting and happiness in the region, noting, however, that the relationship is attenuated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 39 publications
(32 reference statements)
2
27
0
1
Order By: Relevance
“…Este autor concluyó que la participación tiene efectos significativos a nivel individual, como en los sentimientos de eficacia externa; es decir, la creencia de que el régi men o las autoridades son sensibles al intento de influencia del ciudadano. Recientemente, el estudio de la participación política ha generado diversos hallazgos empíricos relevantes (Berinsky & Lenz, 2011;Christensen, 2011;Ekman & Amná, 2012;Marien, Hooghe & Quintelier, 2010;Vráblíková, 2013), y en particular se han incrementado el número y la variedad de estudios dirigidos a evaluar el impacto de distintos tipos de participación política en el bienestar subjetivo, aunque la evidencia presentada hasta ahora no es concluyente (Frey & Stutzer, 2000;2010;WeitzShapiro & Winters, 2011;Flavin & Keane, 2012).…”
Section: B Participación Política Y Bienestar Subjetivounclassified
“…Este autor concluyó que la participación tiene efectos significativos a nivel individual, como en los sentimientos de eficacia externa; es decir, la creencia de que el régi men o las autoridades son sensibles al intento de influencia del ciudadano. Recientemente, el estudio de la participación política ha generado diversos hallazgos empíricos relevantes (Berinsky & Lenz, 2011;Christensen, 2011;Ekman & Amná, 2012;Marien, Hooghe & Quintelier, 2010;Vráblíková, 2013), y en particular se han incrementado el número y la variedad de estudios dirigidos a evaluar el impacto de distintos tipos de participación política en el bienestar subjetivo, aunque la evidencia presentada hasta ahora no es concluyente (Frey & Stutzer, 2000;2010;WeitzShapiro & Winters, 2011;Flavin & Keane, 2012).…”
Section: B Participación Política Y Bienestar Subjetivounclassified
“…Radcliff, ; Frey & Stutzer, 2000a; Di Tella & MacCulloch, ; Tavits, ). On the other hand, recent studies in Europe and Latin America have found that political participation has no direct effects on individuals’ subjective well‐being (Dorn, Fischer, Kirchgässner, & Sousa‐Poza, ; Weitz‐Shapiro & Winters, ; Pirralha, ). More recently, an emerging strand of research has modeled life satisfaction as an independent variable and considered how it affects politics (Weitz‐Shapiro & Winters, ; Flavin & Keane, ; Lorenzini, ).…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, recent studies in Europe and Latin America have found that political participation has no direct effects on individuals’ subjective well‐being (Dorn, Fischer, Kirchgässner, & Sousa‐Poza, ; Weitz‐Shapiro & Winters, ; Pirralha, ). More recently, an emerging strand of research has modeled life satisfaction as an independent variable and considered how it affects politics (Weitz‐Shapiro & Winters, ; Flavin & Keane, ; Lorenzini, ). An important research question that has concerned scholars in this area is whether subjective life satisfaction engenders politically active citizens or whether it breeds political apathy.…”
Section: Introductionmentioning
confidence: 97%
“…According to this literature, two expectations can be formulated. On the one hand, life satisfaction may foster participation in voting (Flavin and Keane 2012;Weitz-Shapiro and Winters 2011). On the other hand, life satisfaction may hinder participation in protest.…”
Section: Hypothesesmentioning
confidence: 99%
“…Several researchers have used subjective well-being to explain political participation (Flavin and Keane 2012;Weitz-Shapiro and Winters 2011;Barnes et al 1979). Others have analyzed it as resulting from political institutions and participation (Tavits 2008;Frey and Stutzer 2000;Dorn et al 2008).…”
Section: Subjective Well-being and Political Participationmentioning
confidence: 99%